High density polyethylene composition with excellent physical properties

The challenges of existing HDPE materials in improving SCR performance and reducing costs are solved by developing polyethylene compositions with a single peak molecular weight distribution and multiple differential crystalline fractions, achieving high SCR performance and low cost production, and maintaining good performance when introducing PCR materials.

CN115989275BActive Publication Date: 2025-03-25EXXONMOBIL CHEMICAL PATENTS INC
View PDF 37 Cites 0 Cited by

Patent Information

Application Number
CN202180052606.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-25
Filing Date
2021-07-26
Publication Date
2025-03-25
Estimated Expiration
2041-07-26

AI Technical Summary

Technical Problem

While existing high-density polyethylene (HDPE) materials improve stress crack resistance (SCR), they have high production complexity and cost, and when introducing post-consumer recycle (PCR) materials, their performance decreases, increasing the possibility of stress crack failure events.

Method used

A polyethylene composition has been developed with a single peak molecular weight distribution and multiple different crystalline fractions, with a density in the range of 0.935 to 0.975 g/cm3 and a melt index in the range of 0.1 to 1 g/10 min. By optimizing the comonomer content and catalyst system, high SCR performance and low cost production are achieved.

Benefits of technology

The polyethylene composition exhibits high environmental stress cracking resistance (ESCR) and excellent impact properties similar to bimodal HDPE, while maintaining good physical properties when blended with PCR materials, reducing material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115989275B_ABST
    Figure CN115989275B_ABST
Patent Text Reader

Abstract

Provided herein are polyethylene compositions having a unimodal molecular weight distribution and exhibiting an excellent balance of physical properties. The polyethylene compositions may have a molecular weight of 0.935 to 0.975 g / cm 3 density and a melt index (I 2.16 ). The polyethylene composition of certain embodiments may exhibit environmental stress crack resistance (ESCR, 10% Igepal, ASTM D1693 Condition B) in the range of 45 to 80 hours, and / or environmental stress crack resistance (ESCR, 100% Igepal, ASTM D1693 Condition B) in the range of 70 to 250 hours. This ESCR is superior to other unimodal resins with similar melt index and density, approaching the ESCR performance of more expensive and complex resins with bimodal molecular weight distribution. The polyethylene composition of certain embodiments may have two distinct crystalline fractions, as shown by temperature rising elution fractionation (TREF).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 070,171, filed on August 25, 2020, entitled “High Density Polyethylene Compositions Having Excellent Physical Properties,” the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to polyolefin compositions, particularly polyethylene homopolymers and copolymers, and articles comprising such polyolefin compositions. Background Art

[0004] High density polyethylene (HDPE) polymer compositions are in high demand for many applications, including various films, pipes (e.g., pressure pipes, corrugated pipes, high temperature resistant or PE-RT pipes), and blow molding. In many of these applications, higher density is beneficial for mechanical strength (e.g., to maintain the internal pressure of the pipe), but negatively affects stress cracking resistance.

[0005] Stress crack resistance (SCR), as demonstrated by good performance in Environmental Stress Crack Resistance (ESCR) and Notched Constant Ligament Stress (NCLS) tests, is particularly important for HDPE based pipe applications and recent industry specifications (e.g., ISO PE 100) are stringent in this regard. Strong SCR performance reduces the likelihood of mechanical or structural failure of the pipe or blow molded article during its life. In addition, strong SCR performance can provide lightweight blow molded articles (e.g., drums, containers, fuel tanks) and reduced film, thereby reducing material consumption and resulting in significant cost savings.

[0006] Generally, HDPE materials follow a trend of SCR as a function of density and melt index (MI); the greater the density and the higher the MI, the lower the SCR of the HDPE / material.

[0007] Some solutions to this include multimodal HDPE compositions having low and high molecular weight fractions to achieve a balance of properties. However, due to their greater production complexity, greater batch-to-batch variability and different processing characteristics compared to unimodal resins, multimodal HDPE compositions tend to be much more expensive.

[0008] Meanwhile, many recent efforts have focused on increasing the use of post-consumer recycled (PCR) polymer materials in forming articles (e.g., blow molded articles, pipes, films, etc.). However, PCR materials alone typically provide much inferior performance to virgin polymers, including SCR and other mechanical properties (in the case of PCR replacing virgin HDPE polymer). A strategy of introducing or blending PCR into virgin polymers is typically employed to achieve a balance of adequate mechanical and other properties while reducing the amount of virgin polymer required for a given application. However, the introduction of any significant portion of PCR into HDPE materials still significantly increases the likelihood of stress cracking failure events.

[0009] References of potential interest in the art include: US 9,493,589; US 2020 / 0224014; US 2020 / 0190238; US 2020 / 0115533; WO 2017 / 112503; WO 2019 / 229209; WO 2020 / 020716.

[0010] There remains a need for new polyolefin compositions, particularly new HDPE compositions, which can achieve excellent stress cracking resistance without the cost of currently available bimodal or multimodal solutions. Such compositions would also ideally enable greater incorporation of PCR materials without adversely sacrificing SCR and other physical properties. Summary of the invention SUMMARY OF THE INVENTION

[0012] In some embodiments, the present disclosure provides a polyethylene composition having a molecular weight of 0.935 to 0.975 g / cm 3 The density is in the range of 0.1 to 1 g / 10 min and the melt index (I 2.16 The polyethylene composition may have a unimodal molecular weight distribution while exhibiting surprisingly high environmental stress crack resistance (ESCR) values ​​comparable to those of polyethylene compositions having a bimodal molecular weight distribution (e.g., ESCR in the range of 45 to 80 hours as measured according to ASTM D1693, Condition B, 10% Igepal; and / or ESCR in the range of 70 to 250 hours as measured according to ASTM D1693, Condition B, 100% Igepal).

[0013] In still other embodiments, the polyethylene composition may also or alternatively have multiple distinct crystalline fractions, as shown by a temperature rising elution fractionation (TREF) plot of dW / dT (derivative of weight % with respect to temperature) vs. T (°C). For example, the multiple distinct crystalline fractions may include (a) a first crystalline fraction having a peak at T1°C on the TREF curve and a second crystalline fraction having a peak at T2°C on the TREF curve, wherein a local minimum at T3°C defines a valley between the peaks of the first and second fractions, further wherein T1 is in the range of 88°C to 92°C, T2 is in the range of 94°C to 100°C, and T3 is in the range of 91°C to 94°C; further provided that T3-T1>1°C and T2-T1>5.5°C. The area A1 under the 1DTREF curve (bounded by T=40°C and T=T3°C) and the area A2 under the 1DTREF curve (bounded by T=T3°C and T=120°C) are such that A1 is at least 15% of the total area A1+A2. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a graph illustrating molecular weight distributions as measured by GPC 4D for polyethylene compositions according to various embodiments of the present disclosure and comparative resins.

[0015] Figure 2a and 2b is a graph illustrating temperature increasing elution fractionation of polyethylene compositions according to various embodiments of the present disclosure and comparative resins.

[0016] Figure 3 is a bar graph showing environmental stress crack resistance (ASTM D1693, 10% Igepal, Condition B) of polyethylene compositions according to various embodiments of the present disclosure and comparative resins.

[0017] Figure 4 is a bar graph showing environmental stress crack resistance (ASTM D1694, 100% Igepal, Condition B) of polyethylene compositions according to various embodiments of the present disclosure and comparative resins.

[0018] Figure 5 is a plot of density versus melt index (MI) for polyethylene compositions according to various embodiments of the present disclosure and comparative resins.

[0019] Figure 6 is a plot showing complex viscosity vs. shear rate (rad / s) for polyethylene compositions according to various embodiments of the present disclosure and comparative resins. DETAILED DESCRIPTION OF THE INVENTION

[0021] The present disclosure relates to polyolefin compositions and articles comprising the same.

[0022] The polyethylene composition according to the present disclosure is a homopolymer of polyethylene, or a majority of ethylene (e.g., 80, 85, 90, 95, 98, 99 wt % or more ethylene-derived units, preferably 98 wt % or more) and one or more C 3 To C 40 Preferably, the polyethylene composition has a melt index (MI, 2.16 kg - also known as I 2 or I 2.16 ) in the range of about 0.20 to about 1.0 (e.g., a density of 0.930 g / cc or more). In addition, these polyethylene compositions are preferably unimodal in molecular weight distribution (as opposed to the more expensive and more complicated to produce bimodal solutions mentioned above), and / or are produced in a single reactor (again, as opposed to many bimodal or multimodal solutions, which are produced in two or more reactors, with each "peak" or fraction attributed to the product of one of the reactors). At the same time, even if produced in a single reactor, the polyethylene compositions of the present disclosure can have at least two distinct crystalline portions or fractions of the polyethylene composition when analyzed by 1-D temperature rising elution fractionation (TREF). In addition, the polyethylene composition can contain trace, but detectable amounts of titanium and / or chromium (e.g., from about 2 ppm to about 4 ppm or 5 ppm Cr, and / or from about 5 or 6 ppm to about 15 or 20 ppm Ti, the ppm values ​​being based on the total mass of the polyethylene composition).

[0023] Without wishing to be bound by theory, it is believed that such polyethylene compositions are "hybrid" compositions which, while unimodal in molecular weight distribution (and / or produced in a single reactor or single reaction step), achieve many of the property advantages typically associated with compositions having multimodal molecular weight distribution (e.g., bimodal, such as those produced in multiple reactors or reactor steps in series).

[0024] For example, compared with other unimodal polyethylene compositions with similar MI and density, polyethylene compositions according to the present disclosure advantageously show very excellent environmental stress cracking resistance (ESCR). Generally, ESCR is considered to be mainly a function of MI and density, making this a surprising result of the polyethylene composition of the present invention, indicating that another property of these compositions leads to their excellent ESCR performance. This is particularly surprising because it is generally expected to achieve greater ESCR by comprising a chain of particularly high molecular weight (e.g., a high molecular weight fraction in a bimodal polyethylene composition), wherein a larger comonomer is introduced on those chains of higher molecular weight. However, in many embodiments, the polyethylene composition of the present invention also does not seem to have high comonomer inclusion in its higher molecular weight chain, and in any case has a very low total comonomer content (e.g., less than 2 wt %, preferably 1 wt % or lower). On the other hand, the polyethylene composition of various embodiments also shows an impact property that is superior to the bimodal polyethylene composition, and it is advantageously compared with the unimodal polyethylene composition instead. Therefore, the polyethylene composition of the present invention achieves an excellent performance balance-close to the bimodal grade in terms of stress cracking resistance, and close to the unimodal grade (and exceeds the bimodal grade) in terms of its impact property.

[0025] Additionally, in particular embodiments, the unimodal polyethylene compositions of the present invention prove to be excellent blending partners for post-consumer recycled (PCR) polymeric materials. For example, blending up to 40, 50, 60 or even 70 weight percent of PCR polymeric material with the polyethylene compositions of the present invention (the weight percents being based on the sum of the PCR polymeric material and the polyethylene composition blended together) allows many of the desired properties of the polyethylene compositions of the present invention to be maintained. This opens up many possibilities for significantly higher inclusion of PCR materials in various articles (e.g., films, bottles, cups, drums, jerry cans, drains, and bags) without the usual attendant sacrifice of the desired properties of the polymers in those articles (e.g., ESCR, flexural properties, stiffness, peak load, and impact properties).

[0026] definition

[0027] The term "polyethylene" refers to a polymer having at least 50 wt % ethylene-derived units, such as at least 70 wt % ethylene-derived units, such as at least 80 wt % ethylene-derived units, such as at least 90 wt % ethylene-derived units, or at least 95 wt % ethylene-derived units, or 100 wt % ethylene-derived units. Polyethylene can therefore be a homopolymer or a copolymer having one or more other monomeric units, including a terpolymer. The polyethylene described herein can, for example, include at least one or more other olefins and / or comonomers.

[0028] "Olefins", or "olefins", are linear, branched or cyclic compounds of carbon and hydrogen having at least one double bond. For purposes of this specification and the claims thereto, when a polymer or copolymer is referred to as containing an olefin, the olefin present in such polymer or copolymer is the polymerized form of the olefin. For example, when a copolymer is said to have an "ethylene" content of 50% to 55% by weight, it is understood that the monomer units in the copolymer are derived from ethylene in the polymerization reaction and the derived units are present at 50% to 55% by weight, based on the weight of the copolymer. A "polymer" has two or more monomer units that are the same or different. A "homopolymer" is a polymer containing the same monomer units. A "copolymer" is a polymer having two or more monomer units that are different from each other. A "terpolymer" is a polymer having three monomer units that are different from each other. Therefore, the definition of copolymer used herein includes terpolymers and the like. The term "different" used in reference to monomer units indicates that the monomer units differ from each other by at least one atom or are isomerically different.

[0029] The term "α-olefin" refers to an olefin having a terminal carbon-carbon double bond in its structure. 1 R 2 C=CH 2 , where R 1 and R 2 are independently hydrogen or any hydrocarbon group; for example, R 1 for hydrogen and R 2 "Linear α-olefin" means a olefin in which R 1 for hydrogen and R 2 An alpha-olefin which is hydrogen or a linear alkyl group.

[0030] For purposes of this disclosure, ethylene shall be considered an alpha-olefin.

[0031] When a polymer or copolymer is referred to herein as comprising an α-olefin (including but not limited to ethylene, 1-butene and 1-hexene), the olefin present in such polymer or copolymer is the polymerized form of the olefin. For example, when a polymer is said to have an "ethylene content" or "ethylene monomer content" of 80 to 99.9 weight percent or to contain 80 to 99.9 weight percent "ethylene-derived units," it is understood that the monomer units in the copolymer are derived from ethylene in the polymerization reaction, and the derived units are present at 80 to 99.9 weight percent, based on the weight of the ethylene content plus the comonomer content.

[0032] When used herein and unless otherwise specified, the term “C n ” refers to hydrocarbon(s) containing n carbon atoms(s) per molecule, where n is a positive integer.

[0033] Polyethylene composition

[0034] In at least one embodiment, the methods described herein produce polyethylene compositions comprising polyethylene homopolymers and / or ethylene with one, two, three, four or more C 3 to C 40 Olefin comonomers (e.g. C 3 To C 20 Copolymers of α-olefin comonomers).

[0035] For example, the polyethylene composition may include C 2 To C 40 Olefins with one, two, three or more different C 2 To C 40 In a particular embodiment, the polyethylene composition comprises a majority of units derived from polyethylene and units derived from one or more C 3 To C 40 Comonomer, preferably C 3 To C 20 Units of α-olefin comonomers such as propylene, 1-butene, 1-hexene, 1-octene, 1-decene, 1-dodecene, preferably propylene, 1-butene, 1-hexene, 1-octene or mixtures thereof, most preferably 1-butene and / or 1-hexene.

[0036] The polyethylene composition can comprise ethylene-derived units in an amount of at least 80 wt% or 85 wt%, preferably at least 90, 95, 96, 97, 98 or 99 wt% (e.g., within a range from a lower limit of 80, 85, 90, 95, 98, 99.0, 99.1, 99.2, 99.3, or 99.4 wt% to an upper limit of 96, 97, 98.1, 98, 98.2, 98.3, 98.4, 98.5, 98.6, 98.7, 98.8, 98.9, 99.0, 99.1, 99.2, 99.3, 99.4, 99.5, 99.6, 99.7, 99.8, or 99.9 wt%, ranges from any of the foregoing lower limits to any of the foregoing upper limits being contemplated with the proviso that the higher value is greater than the lower value). For example, the polyethylene composition may contain 95, 98, 98.5, 99, 99.1, 99.2, or 99.3 to 99.9 weight percent ethylene-derived units. 2 To C 20α-olefin derived units, such as units derived from butene, hexene and / or octane) can be present in the polyethylene composition in a range from a lower limit of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 2.0, 3.0, 4.0, or 5.0 weight percent to an upper limit of 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 3, 4, 5, 10, 15, or 20 weight percent, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated, provided that the upper limit is greater than the lower limit. For example, the polyethylene composition can include 0.1 weight percent to 0.7 weight percent, 0.8 weight percent, 0.9 weight percent, 1.0 weight percent, 1.5 weight percent, or 5.0 weight percent comonomer units.

[0037] Several suitable comonomers have been mentioned, but in various embodiments, other α-olefin comonomers are contemplated. For example, the α-olefin comonomer may be linear or branched, and two or more comonomers may be used if desired. Examples of suitable comonomers include linear C 3 -C 20 α-olefins (such as butene, hexene, octene, etc.) and olefins having one or more C 1 -C 3 Alkyl branched or aromatic alpha-olefins. Specific examples include propylene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene with one or more methyl, ethyl or propyl substituents; 1-hexene with one or more methyl, ethyl or propyl substituents; 1-heptene with one or more methyl, ethyl or propyl substituents; 1-octene with one or more methyl, ethyl or propyl substituents; 1-nonene with one or more methyl, ethyl or propyl substituents; 1-decene substituted with ethyl, methyl or dimethyl; 1-dodecene; and styrene. It goes without saying that the above list of comonomers is merely exemplary and is not intended to be limiting. In some embodiments, the comonomers include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene and styrene.

[0038] In various embodiments, polyethylene composition also includes trace, but titanium and / or chromium of detectable amount.For example, polyethylene composition can be by the amount (with the mass of polyethylene composition) of the upper limit of 3.5ppm, 3.6ppm, 3.7ppm, 3.8ppm, 3.9ppm, 4.0ppm, 4.5ppm or 5.0ppm from the lower limit of 2.0ppm, 2.1ppm, 2.2ppm, 2.3ppm, 2.4ppm or 2.5ppm to 5.0ppm, wherein any aforementioned lower limit to any aforementioned upper limit scope is considered herein.Similarly, polyethylene composition can be by the amount of the upper limit of 13,14,15,16,17,18,19 or 20ppm from the lower limit of 5,6,7 or 8ppm to 10,11,13,14,15,16,17,18,19 or 20ppm to include Ti, also there is the scope from any aforementioned lower limit to any aforementioned upper limit considered herein.

[0039] Polyethylene composition - molecular characteristics

[0040] The polyethylene composition according to various embodiments may have a molecular weight of 0.930 to 0.975 g / cm 3 , for example 0.938 to 0.965 g / cm 3 For example, the ethylene polymer may have a density of from 0.935, 0.938, 0.940, 0.945, 0.950, 0.952, 0.953, 0.954, or 0.955 g / cm 3 The lower limit is 0.957, 0.958, 0.959, 0.960, 0.965, 0.970 or 0.975 g / cm 3 The density of the upper limit of , wherein the range of various embodiments includes any combination of any upper or lower limits disclosed herein. The density herein is measured on a plate using a density gradient column according to ASTM D1505-19 (gradient density). The plate is molded according to ASTM D4703-10a, procedure C, and the plate is conditioned at 23°C for at least 40 hours according to ASTM D618-08 to approach equilibrium crystallinity.

[0041] In various embodiments, the polyethylene composition has one or more, two or more, or preferably all of the following molecular weight properties:

[0042] The weight average molecular weight (Mw) is typically in the range of 90,000 to 300,000, for example, from a lower limit of any one of 100,000 g / mol; 110,000 g / mol; 120,000 g / mol; 130,000 g / mol; 140,000 g / mol; 150,000 g / mol; and 160,000 g / mol to an upper limit of any one of 160,000 g / mol; 170,000 g / mol; 180,000 g / mol; 190,000 g / mol; 200,000 g / mol; 210,000 g / mol; 225,000 g / mol; 250,000; and 300,000 g / mol. In various embodiments, the range from any of the aforementioned lower limits to any of the upper limits is contemplated, provided that the upper limit is greater than the lower limit. For example, in particular embodiments, the Mw may be in the range of 130,000 to 300,000 g / mol, such as 150,000 to 180,000 g / mol; 200,000; 225,000 or 250,000 g / mol.

[0043] The number average molecular weight (Mn) is typically in the range of 5,000 to 30,000, for example, from a lower limit of any one of 5,000 g / mol; 6,000 g / mol; 7,000 g / mol; 8,000 g / mol; 9,000 g / mol to an upper limit of any one of 10,000 g / mol; 11,000 g / mol; 12,000 g / mol; 13,000 g / mol; 14,000 g / mol; 15,000 g / mol; 17,500 g / mol; 20,000 g / mol; 22,500 g / mol; 25,000 g / mol; 27,500 g / mol; and 30,000 g / mol. In various embodiments, ranges from any of the aforementioned lower limits to any of the upper limits are contemplated (e.g., Mn can be in the range of 5,000 g / mol to 15,000 g / mol, e.g., 5,000 or 6,000 g / mol to 11,000 or 12,000 g / mol). More generally, in some embodiments, Mn can be 12,000 g / mol or less, e.g., 11,000 g / mol or less.

[0044] The Z-average molecular weight (Mz) is typically in the range of 700,000 to 3.0 M g / mol, for example, from the lower of any of 700,000 g / mol; 800,000 g / mol; 900,000 g / mol; 1.0 M g / mol; 1.1 M g / mol; 1.2 M g / mol; 1.3 M g / mol; 1.40 M g / mol; 1.45 M g / mol; 1.50 M g / mol; 1.55 M g / mol; and 1.60 M g / mol to 1.65 M g / mol; 1.70 M g / mol; 1.75 M g / mol; 1.80 M g / mol; 1.85 M g / mol; 1.90 M g / mol; 1.95 M g / mol; 2.0 M g / mol; 2.5 M g / mol; 2.75 M g / mol; and 3.0 M g / mol. In various embodiments, the range from any of the aforementioned lower limits to any of the upper limits is considered (e.g., Mz can be in the range of 1.0M to 3.0M g / mol, such as 1.5M to 3.0M g / mol, or 1.50M to 2.0M g / mol, such as 1.60M to 1.65M g / mol). In specific embodiments, Mz can be at least 1.0M g / mol, such as at least 1.50M g / mol, or at least 1.60M g / mol, and the upper limit is not necessarily considered.

[0045] ·Z plus 1 average molecular weight (M z+1 ) is within the range of a lower limit of any of 2.75M, 3.0M, 3.25M, 3.5M, or 3.75M g / mol to an upper limit of any of 4.0M, 4.1M, 4.2M, or 4.5M g / mol, wherein a range from any of the foregoing lower limits to any of the foregoing upper limits is contemplated (e.g., 3.5M g / mol to 4.2M g / mol, or 2.75M g / mol to 4.5M g / mol, e.g., 3.75M to 4.5M g / mol). In certain embodiments, M Z+1 It may be at least 3.5 M, such as at least 3.75 Mg / mol, with the upper limit not necessarily being considered.

[0046] In addition, the polyethylene composition according to various embodiments can have an Mw / Mn value (sometimes also referred to as a polydispersity index, PDI) in the range of 10, 12, 15 or 16 to 17, 18, 19, 20, 22, 25, 26 or 27 (ranges from any lower limit to any upper limit are contemplated, such as Mw / Mn of 12 to 25 or 15 to 20). Similarly, the Mz / Mw ratio of the polyethylene composition of various embodiments is in the range of 5, 6, 7, 8 or 9 to 10, 11, 12, 13, 14, 15, 17 or 20 (ranges from any lower limit to any upper limit are contemplated, such as Mz / Mw of 5 to 15, such as 7 to 12). The Mz / Mn ratio (indicating the breadth of the overall distribution of molecular weights among the chains within a polymer by considering two characteristic values ​​of very high molecular weight chains (Mz) and very low molecular weight chains (Mn)) can be in the range of 100, 110, 115, 120, 125, 130, 135 or 140 to 150, 160, 170, 180, 190, 200, 250, 300, 350 or 400 (considering the range of any lower limit to any upper limit, for example, Mz / Mn is 110 to 250, or 130 to 200, for example, 140 to 160). In certain embodiments, the Mz / Mw ratio can be at least 8, 9 or 10, without necessarily requiring a specific upper limit. Similarly, in certain embodiments, the Mz / Mn ratio can be at least 130, for example, at least 140, at least 145, 150 or at least 160, without necessarily requiring any upper limit.

[0047] In addition, as noted, the polyethylene compositions of the various embodiments described herein exhibit a unimodal molecular weight distribution, which refers to the presence of a single distinguishable peak in the molecular weight distribution curve of the composition (as determined using gel permeation chromatography (GPC) or other recognized analytical techniques, noting that if there is any conflict between or among analytical techniques, the molecular weight distribution determined by GPC as described below shall control). Examples of "unimodal" molecular weight distributions can be found in U.S. Pat. No. 8,691,715, the disclosure of which is incorporated herein by reference. Figure 6 , which is incorporated herein by reference. This is in contrast to a "multimodal" molecular weight distribution, which refers to the presence of at least two distinguishable peaks in the molecular weight distribution curve (again, as determined by GPC or any other recognized analytical technique, in which case GPC controls in the event of any conflict). For example, if there are two distinguishable peaks in the molecular weight distribution curve, then such a composition may be referred to as a bimodal composition. For example, in the '715 patent, the Figure 1-5Representative bimodal molecular weight distribution curves are shown. In these figures, there are valleys between peaks, and the peaks can be independent or deconvoluted. In general, bimodal molecular weight distributions are characterized as having an identifiable high molecular weight component (or distribution) and an identifiable low molecular weight component (or distribution). For examples of molecular weight distributions of exemplary polyethylene composition embodiments (I-1, I-2, and I-3) according to the present disclosure and comparative HDPE C-1, see also the Figure 1 , wherein the distribution of each of the foregoing exhibits a single peak for those exemplary compositions; whereas, in contrast, Figure 1 The comparative HDPE C-2 has a bimodal distribution (in the center of the molecular weight distribution graph, two peaks of C-2 can be seen).

[0048] In addition to exhibiting a unimodal distribution of molecular weights, in certain embodiments, the polyethylene composition may exhibit a long "high molecular weight tail" in a plot of molecular weight fractions from a GPC measurement (the GPC measurement method is described in detail below). Figure 1 Also shown is this long high molecular weight tail (150) of the inventive examples therein. In this unimodal embodiment, this long "high molecular weight tail" can contribute to favorable physical properties. In addition, the Mz, Mz+1 and / or Mz / Mn values ​​according to the above ranges can be used to quantitatively indicate the presence of this long "high molecular weight tail".

[0049] The polyethylene composition according to various embodiments may have a g' value (also referred to as g'vis, branching index, or long chain branching (LCB) index) equal to or greater than 0.92, 0.93, or 0.94. For example, g' may be in the range of 0.90, 0.91, 0.92, 0.93, or 0.94 to 0.95, 0.96, 0.97, 0.98, 0.99, or 1.0 (considering ranges from any of the foregoing lower limits to any of the foregoing upper limits, e.g., 0.90 to 0.97 or 0.93 to 0.95).

[0050] The distribution and moment of molecular weight (Mw, Mn, Mz, Mw / Mn, Mz / Mn, etc.) and monomer / comonomer content (C 2 , C 4 , C 6 and / or C 8And / or other, etc.) and long chain branching index (g') are determined by using a high temperature gel permeation chromatography (Polymer CharGPC-IR) equipped with a multi-channel bandpass filter-based infrared detector IR5, an 18-angle light scattering detector and a viscometer. Three Agilent PLgel 10μm mixed-B LS columns are used to provide polymer separation. The detailed analytical principles and methods for molecular weight determination are described in paragraphs

[0044] -

[0051] of PCT Publication WO2019 / 246069A1, which are incorporated herein by reference (note that the formula c= / / / for the concentration (c) at each point in the chromatogram cited in paragraph

[0044] is c=βI, where β is a mass constant and I is the IR5 broadband signal intensity (I) minus the baseline). Unless otherwise noted, all molecular weight moments used or referred to in this disclosure are determined according to conventional molecular weight (IR molecular weight) determination methods (e.g., as cited in paragraphs

[0044] -

[0045] of the just-mentioned disclosure), noting that for the formula in this paragraph

[0044] , a=0.695 and K=0.000579 (1-0.75 Wt) are used, where Wt is the weight fraction of the hexane comonomer, and also noting that the comonomer composition is determined by the corresponding CH 2 and CH 3 The ratio of the IR5 detector intensity of the PE channel calibrated with a series of PE and PP homopolymer / copolymer standards with nominal values ​​predetermined by NMR or FTIR (providing methyl (CH 3 / 1000TC)), as indicated in paragraph

[0045] of the PCT publication just mentioned).

[0051] On the other hand, the branching index g'LCB (also called g'vis) is determined using light scattering (LS) according to the method described in paragraphs

[0048] -

[0051] of PCT Publication WO2019 / 246069A1.

[0052] Crystallinity

[0053] In addition, the polyethylene compositions of various embodiments exhibit at least two distinct crystalline fractions, as determined by temperature rising elution fractionation (TREF) using an IR detector. Temperature rising elution fractionation (TREF) analysis for the purposes of the figures reported herein was performed using a crystallization elution fractionation (CEF) instrument from Polymer Char, SA, Valencia, Spain. A general description of the principles of CEF analysis and the specific apparatus used is given in the article Crystallization Elution Fractionation: A New Separation Process for Polyolefin Resins, Monrabal, B. et al., Macromol. Symp. 2007, 257, 71. In particular, the method according to the Monrabal article was used. Figure 1 The method of "TREF separation method" shown in a, wherein F c =0. The relevant details of the analytical method and the characteristics of the equipment used are as follows. The solvent used to prepare the sample solution and elution is 1,2-dichlorobenzene (ODCB) filtered using a 0.1-μm Teflon filter (Millipore). The sample to be analyzed (16 mg) is dissolved in 8 ml of ODCB measured at ambient temperature by stirring at 150° C. (medium setting) for 90 min. First, a small volume of the polymer solution is filtered through an online filter (stainless steel, 10 μm), which is backwashed after each filtration. The filtrate is then used to completely fill the 200-μl injection valve loop. The volume in the loop was then introduced near the center of a CEF column (15 cm long SS tubing, 3 / 8″ OD, 7.8 mm ID) packed with an inert support (SS balls) at 140°C and the column temperature was stabilized at 125°C for 20 min. The sample volume was then allowed to crystallize in the column by lowering the temperature to 0°C at a cooling rate of 1°C / min. The column was kept at 0°C for 10 min and then ODCB fluid (1 ml / min) was injected into the column for 10 min to elute and measure the non-crystallized polymer (soluble fraction). The broadband channel of the infrared detector used (Polymer Char IR5) produced an absorption signal that was proportional to the polymer concentration in the elution stream. A complete TREF curve was then generated as follows: the temperature of the column was increased from 0°C to 140°C at a rate of 2°C / min while maintaining an ODCB flow of 1 ml / min to elute and measure the concentration of dissolved polymer. The TREF curve was further processed as follows:

[0054] The instrument's solvent-only response is generated and subtracted from the sample's TREF curve. The solvent-only response is generated by running the same method as for the polymer sample, typically prior to the method, but without adding any polymer to the sample vial; using the same solvent reservoir as the polymer sample, and without replenishing fresh solvent; and within reasonable proximity of the run of the polymer sample.

[0055] The temperature axis of the TREF curve is appropriately shifted to correct for the delay in the IR signal caused by the column to detector volume. This volume is obtained by first using a HDPE resin or by using a narrow band filter of the IR5 detector (the filter is adjusted to CH 2 and CH 3 Any other resin or material (including, for example, eicosane (C 20 The injection valve loop is filled with a ~1 mg / ml solution of n-alkanes) and the loop volume is then loaded at the same position in the column where the sample is loaded for TREF analysis; the hot solution is then directed to the detector using an isothermal method at a constant flow rate of 1 ml / min; the time after injection when the HDPE (or other substance according to the instructions just given) probe peak appears in the IR signal is then measured. Therefore, the delay volume (ml) is equivalent to the time (min). This standard calibration procedure can also be found in the Polymer Char manual for CEF instruments.

[0056] The curve is baseline corrected and appropriate integration limits are selected (see below for upper and lower temperature limits for integration limits), and the curve is normalized so that the area of ​​the curve is 100 wt % (after selecting the integration limits so that a preferred wt % of the polymer sample (e.g., at least 95%, 96%, 97%, 98% or even 99%) is captured by the integration, again as described below).

[0057] The polyethylene compositions of the present invention of various embodiments exhibit two or more well-defined peaks in the TREF curve, wherein there are valleys between the peaks, and the peaks can be separated (or deconvoluted). For example, Figure 2a and 2b A comparison between inventive examples I-1, I-2 and I-3 and comparative HDPEs (C-1, with unimodal molecular weight distribution, and C-2, a typical bimodal molecular weight HDPE) is shown. Figure 2a is a plot of the weight % of polymer eluted (y-axis) at different temperatures (x-axis) when following the TREF procedure described above. Figure 2b It is painted Figure 2a, zoomed in on the first peak exhibited by the inventive polymer samples. In particular, as can be seen, the inventive examples have a clear peak at about 89°C, eluting with an adjacent valley at about 92°C, in addition to a clear (and higher) peak at about 97°C (exhibited by both the inventive examples and the comparative examples); whereas the C-2 (bimodal molecular weight) HDPE exhibits a shoulder with no decrease in weight % eluting as the TREF procedure proceeds from 89°C upward, and the C-1 (unimodal molecular weight) HDPE exhibits a plateau (with perhaps a very slight decrease) at 91-94°C. Expressed in mathematical terms, the inventive examples demonstrate three flips in the second derivative of dW / dT versus temperature (°C) in the TREF plot - specifically, two flips from positive to negative (peaks) at about T=T1=89°C and about T=T2=97°C and one flip from negative to positive (valley) at about T=T3=92°C. In addition, the ( ) from the first peak (at T=T1) to the valley (T=T3) is not significantly different from the ( ) second derivative of dW / dT versus temperature (°C) in the TREF plot. Figure 2b The dW / dT or Y-axis value in the figure varies between about 0.25 and 0.5 wt% / °C, particularly between about 0.3 and 0.4 wt% / °C, with reference to Figure 2b .

[0058] The polyethylene compositions according to various embodiments can be further defined according to the area under each segment of the dW / dT (derivative of elution weight % with respect to temperature) versus temperature function generated by a TREF plot. Figure 2a and 2b , the curve can be divided into regions associated with lower temperature eluting crystallinity fractions (lower crystallinity) and higher crystallinity fractions by using the distinct valleys between the peaks at x = T3 (in these embodiments, about 92°C as indicated) as dividing points. That is, the TREF curve itself can be considered to be generally composed of two parts for the area under such a curve: a portion or area A1 that is the range of x (temperature) values ​​from x = 40°C to x = T3 (at Figure 2a and 2b In the case of T3 = 92 ° C); and the range of the portion or area A2 as the x value is x = T3 ( Figure 2a and Figure 2b = 92°C in the example above) to x = 120°C. In other words, A1 is the area under the curve associated with one or more first lower crystallinity fractions of the polyethylene composition (i.e., associated with the first peak at T1) and the rest of the composition eluting at a temperature lower than T1; and A2 is the area under the curve associated with the second higher crystallinity fraction of the polyethylene composition; wherein the valley between the two main peaks (T3, which can also be labeled as the peak minimum temperature between T1 and T2) is used as the dividing line.

[0059] It should be noted that the upper and lower limits (40°C and 120°C, respectively) for defining the temperatures of A1 and A2 are selected to ensure adequate coverage of the total area under the TREF curve, preferably at least 95% of the total area. In other embodiments, it is contemplated that other extreme low-end and high-end temperatures may be used. However, a low temperature (e.g., 120°C, 40°C, 120°C, respectively) below the first significant elution (y value of 1 or greater in the TREF curve) should be used. Figure 2a In theory, any temperature below 50°C can be used, although it is preferred to define a minimum temperature that is well below the first significant elution (e.g., at least 10°C lower). Likewise, a high temperature above the last significant elution on the TREF curve should be used (e.g., according to Figure 2b At least 105°C), but again preferably at least 10°C above the last significant elution. In an exemplary case, low T = 40°C and high T = 120°C are selected as boundaries for the total integration, and 98% of the total area under the curve is covered. Therefore, in other words, in some embodiments, it is preferred that the upper and lower limits of the integration of the TREF curve used to determine the total area (for the purposes of the A1 and A2 fractions) are such that at least 95%, preferably at least 96%, more preferably at least 97%, for example at least 98%, or even 99% of the total area under the TREF curve is covered (before normalization to 100% by weight, as discussed above in conjunction with the TREF procedure).

[0060] In addition, to further ensure that a suitably strong valley is identified between the two crystallinity peaks, the following conditions are also preferably met in the polyethylene composition having a crystallinity according to various embodiments herein: T3-T1>1°C and T2-T1>5.5°C. In other words, when a distinct valley is observed to be more than 1°C higher than the first peak (at x=T1), for the purposes of these embodiments, the distinct valley can be considered to exist on the TREF curve; in addition, the elution temperature difference between the two crystallinity peaks (x=T1 and x=T2) is greater than 5.5°C. In these cases, it can be confirmed that there are two distinct crystallinity peaks, with distinct valleys.

[0061] In addition, it should be noted that T1, T2 and T3 are not necessarily identical to those in the embodiments exemplified herein. For example, in various embodiments, T1 may be in the range of a lower limit of 80, 81, 82, 84, 85, 86, 87, 88 or 89° C. to an upper limit of 90, 91, 92, 93 or 94° C.; T3 may be in the range of a lower limit of 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 or 92° C. to an upper limit of 92, 93, 94, 95 or 96° C.; and T2 may be in the range of a lower limit of 92, 93, 94, 95 or 96° C.; to an upper limit of 96° C., 97° C., 98° C., 99° C. or 100° C., wherein a range from any lower limit to any upper limit is considered (provided that the upper limit is greater than the lower limit). For example, T1 may generally be in the range of 80-94° C.; T3 may be in the range of 82-96° C.; and T2 may be in the range of 92-100° C. Furthermore, in various embodiments of these embodiments, T1, T2 and T3 preferably follow the conditions just indicated (T3-T1>1° C.; T2-T1>5.5° C.).

[0062] Following these definitions of the TREF curve area, the polyethylene compositions according to various embodiments of the present disclosure exhibit an area A1 that is 15% or greater of the total area under the entire curve (i.e., A1 plus A2, or the area under the curve when x changes from T = 40°C to T = 120°C); and an area A2 that is at most 85% of the total area under the curve. In various embodiments, A1 may be at least 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0%, 24.0%, 25.0%, 27%, or even 30.0% of the total area under the curve (A1 plus A2), with A2 constituting the remainder of such area %. This helps to quantify the deconvolution between the first and second distinct fractions of crystallinity in the polyethylene compositions of such embodiments. Without wishing to be bound by theory, it is believed that the presence of additional distinct fractions of crystalline polymer within the polyethylene composition provides some advantageous properties approaching or even matching those of a polyethylene composition having a multimodal molecular weight distribution.

[0063] Other rheological properties

[0064] In various embodiments, the polyethylene composition has a melt index (MI, also referred to as I in the case of a 2.16 kg load used in the identification test) in the range of 0.1 g / 10 min to 5 g / 10 min, such as from a lower limit of any one of 0.1, 0.2, and 0.3 g / 10 min to an upper limit of 0.5, 0.55, 0.60, 0.65, 0.70, 0.75, 1.0, 1.2, 1.5, 1.7, 2.0, 3.0, 4.0, 5.0, or 10.0 g / 10 min. 2 or I2.16 ), wherein the range of any of the foregoing lower limits to any of the foregoing upper limits is contemplated herein (e.g., 0.1 to 1.0 or 2.0 g / 10 min, such as 0.3 to 0.5 g / 10 min). In addition, the polyethylene compositions of various embodiments may have a high load melt index (HLMI) (recognizing the 21.6 kg load used in the test, also referred to as I ) in the range of a lower limit of 20, 25, 28, 29, 30, or 31 g / 10 min to an upper limit of 35, 36, 37, 38, 39, 40, 45, 50, 60, 70, or 75 g / 10 min. 21 or I 21.6 ); wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated herein (e.g., 25 to 50 g / 10 min, such as 30 to 40 g / 10 min).

[0065] The polyethylene composition according to various embodiments may have a melt index ratio (MIR, defined as I ) in the range of a lower limit of any of 60, 65, 70, 75, 80, 81, 82, 83, 84, or 85 to an upper limit of 88, 89, 90, 91, 92, 93, 94, 95, 100, or 110. 21.6 / I 2.16 ); wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 60 to 100, such as 80 or 85 to 94 or 95) are contemplated herein.

[0066] Melt index (2.16kg) and high load melt index (HLMI, 21.6kg) values ​​can be measured according to ASTM D1238-13 procedure B, for example, by using a Gottfert MI-2 series melt flow indexer. For the MI, HLMI and MIR values ​​reported herein, the test conditions were set at 190°C and 2.16kg (MI) and 21.6kg (HMLI) loads. At 190°C, 5g to 6g of sample were loaded into the barrel of the instrument and manually compressed. Then, the material was automatically compacted into the barrel by lowering all available weights onto the piston to remove all bubbles. Data collection was started after 6 minutes of pre-melting time. In addition, samples were pressed through a die head of 8mm length and 2.095mm diameter.

[0067] In various embodiments, the polyethylene composition shows shear thinning rheology, which means that for increasing shear rate, viscosity decreases. However, advantageously, even at low shear rates (less than 1rad / s, preferably less than 0.5rad / s, for example, at 0.1 and 0.01rad / s), the complex viscosity of the polyethylene composition of these embodiments is also relatively low. This rheology shows good processability (as long as the viscosity that the shear rate simulation composition can show when processed in an extruder or similar device) of the polyethylene composition of such embodiments. Therefore, the polyethylene composition according to various embodiments can show one or more of the following rheological properties, preferably two or more, or even all:

[0068] The shear thinning degree DST is within the range of a lower limit of 0.965, 0.970 or 0.975 to an upper limit of 0.980, 0.985 or 0.990, and the range of any of the foregoing lower limits to any of the foregoing upper limits (e.g., 0.975 to 0.980) is contemplated herein. DST is a measure of shear thinning rheological behavior (viscosity decreases with increasing shear rate) and is defined as DST = [η*(0.01 rad / s) - η*(100 rad / s)] / η*(0.01 rad / s), wherein η*(0.01 rad / s) and η*(100 rad / s) are the complex viscosities at 0.01 rad / s and 100 rad / s, respectively.

[0069] · A complex viscosity (at 628 rad / s, 190°C) of 800, 700, 600, 500 or 450 Pa*s or less; for example, within the range of a lower limit of 200, 250, 300, 350, 400, 450, 500 or 550 Pa*s to an upper limit of 300, 350, 400, 450, 500, 550, 600, 650, 700, 750 or 800 Pa*s, with ranges from any of the foregoing lower limits to any of the foregoing upper limits (provided that the upper limit is greater than the lower limit) (e.g., 200 to 800 Pa*s, e.g., 300 to 500 Pa*s).

[0070] · Complex viscosity (at 100 rad / s, 190°C) in the range of 3,000 Pa*s or less; such as 2,000; 1,900; 1,800; or 1,500 Pa*s or less; for example, a lower limit of 900; 1,000; 1,200; 1,300 or 1,350 to an upper limit of 1,300; 1,400; 1,500; 1,750; 2,000; 2,250; 2,500; 2,750 or 3,000 Pa*s, wherein ranges from any lower limit to any upper limit (provided that the upper limit is greater than the lower limit) (e.g., 900 to 3,000 Pa*s, e.g., 1,200 to 1,500 Pa*s) are contemplated herein.

[0071] 100,000 Pa*s or less; for example 80,000 Pa*s or less; or 75,000 Pa*s or less; or 65,000 Pa*s or less; or in some cases 10,000; 15,000; 20,000; 30,000; 45,000; 50,000; or 55,000 Pa*s to a lower limit of 60,000; 65,000; 70,000; 75,0 00; 80,000; 85,000; 90,000; 95,000 or 100,000 Pa*s, and ranges from any lower limit to any upper limit (provided that the upper limit is greater than the lower limit) are considered herein (e.g., 10,000 Pa*s to 100,000 Pa*s, e.g., 50,000 Pa*s to 75,000 Pa*s).

[0072] In particular embodiments, the polyethylene composition may be characterized by a combination of rheological and microstructural parameters according to the following relationship:

[0073]

[0074] where HLMI (or equivalently, I 21.6 ), Mz and Mn are as defined previously, η 低 It is the complex viscosity at 628rad / s. This relationship may be referred to herein as "high-low ratio", because it provides the ratio of high molecular weight polymer chain group to low molecular weight polymer chain group in the polyethylene composition, and also illustrates low viscosity rheological behavior. According to the high-low ratio of various polyethylene compositions disclosed herein, any lower limit of 8, 9, 10, 10.5, 11, 11.5 or 12.0 may be in the range of any upper limit of 14, 14.5, 15.0, 15.5, 16.0, 16.5, 17, 18, 19 or 20, wherein any aforementioned lower limit to any aforementioned upper limit is considered herein (e.g., 8 to 20, 10 to 20, 10 to 16, 10 to 15.5, etc.).

[0075] Rheological data, such as complex viscosity, were determined using SAOS (Small Amplitude Oscillatory Shear) tests. SAOS experiments were performed at 190°C using a 25 mm parallel plate configuration on an ARES-G2 (TA Instruments). Sample test discs (25 mm diameter, 2 mm thickness) were prepared at 190°C using a Carver laboratory press. The samples were allowed to rest for approximately 3 minutes without pressure to melt, and then typically maintained under pressure for 3 minutes to compression mold the samples. The disc samples were first balanced between parallel plates in a rheometer at 190°C for approximately 10 minutes to clear any preheating and crystallization history. Next, an angular frequency sweep was performed from 628 rad / s to 0.01 rad / s angular frequency using 5 points / decade and strain values ​​within the linear viscoelastic region determined from strain sweep experiments (see CW Macosko, Rheology Principles, Measurements and Applications (Wiley-VCH, New York, 1994) with a typical gap of 1.5 mm. All experiments were performed in a nitrogen atmosphere to minimize any degradation of the sample during rheological testing.

[0076] To quantify the shear-thinning rheological behavior, which is defined as the decrease in viscosity as the frequency or shear rate increases, we define the shear-thinning degree (DST) parameter. DST is measured by the following expression:

[0077] DST=[η*(0.01rad / s)-η*(100rad / s)] / η*(0.01rad / s)

[0078] Where η*(0.01 rad / s) and η*(100 rad / s) are the complex viscosities at 0.01 rad / s and 100 rad / s, respectively. The complex viscosity values ​​are shown only to emphasize that the resins of the present invention show lower viscosity values ​​at 0.01 rad / s than the control samples, but all resins have substantially the same DST and comparable viscosity at 628 rad / s.

[0079] Other physical properties

[0080] Polyethylene compositions according to certain embodiments exhibit highly favorable environmental stress crack resistance (ESCR), particularly for compositions exhibiting unimodal molecular weight. It is believed that the ESCR of these unimodal compositions can surprisingly approach or possibly even exceed the ESCR achieved with bimodal polyethylene grades in some cases. ESCR is measured according to ASTM D 1693 Condition B at 10% or 100% Igepal (octylphenoxy-polyethoxy-ethanol, a nonionic, non-denaturing detergent used as a stress crack accelerator).

[0081] The polyethylene compositions of various embodiments exhibit an ESCR (10% Igepal) in the range of a lower limit of 45, 46, 47, 48, 49, 50, 51, 52, 53, 54 or 55 hours to an upper limit of any of 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 75 or 80 hours, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated (e.g., 45 to 75 hours, e.g., 50 to 70 hours or 50 to 65 hours). Additionally or alternatively, the polyethylene composition may exhibit an ESCR (100% Igepal) in a range from a lower limit of 50, 60, 70, 80, 85, 90, 95, or 100 hours to an upper limit of 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 225, or 250 hours, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated (e.g., 80 to 250 hours, such as 80 to 175 hours or 85 to 150 hours).

[0082] The polyethylene compositions of various embodiments may additionally or alternatively exhibit one or more, two or more, or even all of the following impact properties:

[0083] Izod (I) within a range of 1.2, 1.5, 1.6, 1.7 or 1.8 Ft-lb / in on the lower end to 2.0, 2.2, 2.3, 2.4, 2.5, 2.7, 2.8, 2.9 or 3.0 Ft-lb / in on the upper end ZOD ) Impact Strength (23°C, ASTM D256 Method A), wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated (e.g., 1.2 to 3.0 Ft-lb / in, e.g., 1.8 to 2.5 or 1.8 to 2.4 Ft-lb / in).

[0084] Izod impact strength (-40°C, ASTM D256 Method A) within a range of a lower limit of 1.00, 1.01, 1.02, 1.03, 1.04, or 1.05 Ft-lb / in to an upper limit of 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, or 1.20 Ft-lb / in, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated (e.g., 1.00 to 1.20 Ft-lb / in, e.g., 1.00 to 1.15 or 1.00 to 1.10 Ft-lb / in).

[0085] 6, 7, 7.1, 7.2, 7.5, 7.7, 7.8, 8.0, 9.2, 8.4 or 8.5 kJ / m 2The lower limit is 9.0, 9.1, 9.2, 9.5, 9.8, 10.0 or 10.5 kJ / m 2 The Charpy Impact Strength, also known as the Charpy V-notch test (ISO 179_1 / 1eA), in the range of any of the foregoing lower limits to any of the foregoing upper limits (e.g., 7 to 10.5, e.g., 7.1 or 7.2 to 9.5 or 10.0 KJ / m 2 ). The Charpy impact strength is a standardized high strain rate test that determines the amount of energy absorbed by a material during fracture. The quantitative result of the impact tests the energy required to break a material and can be used to measure the toughness of a material. It can be determined using equipment from Empire Technologies Inc. according to the ISO method described above.

[0086] The polyethylene compositions of various embodiments may additionally or alternatively exhibit one or more, two or more, or even all of the following additional physical properties:

[0087] - Notched Constant Tensile Stress (NCLS) (per ASTM F2136; 10% Igepal, 50°C, 600 psi; wherein the sheet is made by compression molding according to ASTM D4703) in a range of a lower limit of 10, 11, 12, 13, or 14 hours to an upper limit of 14, 15, 16, 17, 18, 19, 20, 22, 24, or 25 hours, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 10 to 20, e.g., 13 to 20 or 13 to 18) are contemplated.

[0088] A Shore D hardness (ASTM D2240) within a range of a lower limit of 55, 60, 61, or 62 to an upper limit of 62, 63, 64, 65, 66, 68, or 70, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 55 to 70, e.g., 60 to 65 or 60 to 62) are contemplated.

[0089] A Vicat softening temperature (ASTM D1525, 10 N at 50°C / hr) in a range of a lower limit of 115, 118, 120, 121, 122, 123, 124.0, 124.1, 124.2, or 124.3°C to an upper limit of 124.8, 124.9, 125.0, 125.1, 125.4, 125.5, 125.6, 126.0, 127.0, 130.0, or 135.0°C, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 124.0 to 130.0°C, e.g., 124.0 to 126.0°C, or 124.0 to 124.8°C) are contemplated.

[0090] A tensile stress at yield (ASTM D638 using Type IV tensile bars compression molded according to ASTM D4703 and die cut at a test speed of 2 in / min) in the range of 3800, 3900, 3950, 3990, 4000, 4020, or 4030 psi on the lower limit to 4050, 4070, 4080, 4090, 4100, or 4150 psi on the upper limit, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 3800 to 4150, e.g., 3990 to 4050) are contemplated. The tensile stress at the yield point is the first point on the stress-strain curve where an increase in strain occurs without an increase in stress.

[0091] Flexural 1% secant modulus within a range of a lower limit of 140, 150, 160, 165, 170, or 180 in / min to an upper limit of 190, 195, 200, 205, 210, 215, or 220 in / min, wherein a range from any of the foregoing lower limits to any of the foregoing upper limits is contemplated (e.g., 150 to 220 in / min, such as 165 to 200 in / min or 170 to 200 in / min). Flexural properties of polymers may be obtained following ASTM D 790, Proc. B. The secant modulus is the ratio of the stress at any selected point on a stress-strain curve to the corresponding strain, i.e., the slope of the straight line connecting the origin and the selected point on the actual stress-strain curve. The 1% secant modulus is calculated at 1% tensile strain using the following formula: Secant modulus = (σ2-σ1) / (ε2-ε1) = (stress@1% strain-0) / (1% strain-0), noting that the flexural stress σ and flexural strain ε are based on ASTM D790-17.

[0092] Method for preparing polyethylene composition

[0093] The polymerization process of the present disclosure can be carried out in any suitable manner known in the art. Any suspension, homogeneous, bulk, solution, slurry or gas phase polymerization process known in the art can be used. These methods can be operated in batch, semi-batch or continuous mode. A homogeneous polymerization process is defined as a process in which at least about 90wt% of the product is soluble in the reaction medium. A bulk process is defined as a process in which the monomer concentration in all the raw materials of the reactor is 70 volume % or higher. Alternatively, a solvent or diluent is not present in or added to the reaction medium (except for a small amount used as a carrier for the catalyst system or other additives, or an amount usually used in conjunction with the monomer, such as propane in propylene).

[0094] In a specific embodiment, the method is a slurry polymerization process, preferably a continuous slurry loop polymerization process. A single slurry loop reactor can be used, or multiple reactors in parallel or in series (although in order to achieve a unimodal molecular weight distribution according to various embodiments, as previously described, it is preferred to use a single reactor, or use the same catalyst, feed and reaction conditions in multiple reactors (e.g., in parallel), so that the composition is considered to be prepared in a single reaction step). The term "slurry polymerization process" as used herein refers to a polymerization process in which a supported catalyst is used and monomers are polymerized on supported catalyst particles in a liquid medium (comprising, for example, an inert diluent and unreacted polymerizable monomers) so that a two-phase composition comprising polymer solids and liquids circulates in a polymerization reactor. Typically, a slurry tank or a slurry loop reactor can be used; in a specific embodiment here, a slurry loop reactor is preferred. In such a method, a reaction diluent, dissolved monomers and catalysts circulate in a loop reactor, wherein the pressure of the polymerization reaction is relatively high. The solid polymer produced is also circulated in the reactor. The slurry of polymer and liquid medium may be collected in one or more settling legs of the slurry loop reactor from which the slurry is periodically discharged to a flash chamber wherein the mixture is flashed to a relatively low pressure; as an alternative to the settling legs, in other instances, a single point discharge method may be used to move the slurry to the flash chamber. The flashing results in substantially complete removal of the liquid medium from the polymer, and the evaporated polymerization diluent (e.g., isobutane) is then recompressed to condense the recovered diluent into a liquid form suitable for recycling as liquid diluent to the polymerization zone. The cost of the compression equipment and the facilities required for its operation generally account for a large portion of the expenses involved in preparing the polymer.

[0095] Suitable slurry polymerization processes for implementing such embodiments are described, for example, in U.S. Pat. No. 6,204,344 at column 8, line 30 to column 9, line 48. Figure 1, which portions are incorporated herein by reference; the entire contents of the '344 patent are incorporated herein by reference in jurisdictions in which such incorporation is permitted. Generally speaking, the '344 patent describes embodiments of a slurry polymerization system including a two-stage flash system for diluent recovery and recycle and associated methods for diluent recovery and recycle. In particular, the '344 patent discloses an apparatus for continuously recovering polymer solids from a polymerization effluent comprising a slurry of the polymer solids in a liquid medium comprising an inert diluent and unreacted monomers, which apparatus may be used in embodiments according to the present disclosure (although other slurry polymerization systems and apparatus may be used in accordance with various other embodiments as well). The apparatus described in the '344 patent includes a discharge valve on a slurry reactor, examples of which include a slurry loop reactor and a stirred tank slurry reactor, for continuously discharging a portion of the slurry reactor contents into a first flash tank. The first flash tank is operated at a pressure and slurry temperature such that a majority of the liquid medium will evaporate and the inert diluent component of the vapor can be condensed by heat exchange with a fluid without compression. The first flash tank is in fluid communication with the second flash tank via a pressure seal that allows a plug flow of concentrated slurry into the second flash tank, which is operated at the temperature and pressure of the concentrated polymer solids / slurry so that any remaining inert diluent and / or unreacted monomer will be vaporized and removed from the top of the tower for condensation by compression and heat exchange, and polymer solids are discharged from the bottom of the second flash tank for additional processing or storage. A complete polymer production plant will include many of these and other components (e.g., components for handling solids, liquids, and gases, such as, but not limited to, separator systems, such as cyclones and collector drums; pumps; sensors or meters for flow, pressure, and / or temperature, etc.), which are not described in detail herein. Unless otherwise specified herein, these components are considered to be known in the art.

[0096] The liquid diluent used in the polymerization medium is generally an alkane containing 3 to 7 carbon atoms. The medium used should be liquid and relatively inert under the polymerization conditions. In some embodiments, branched alkanes are preferred diluents. In other embodiments, hexane or isobutane diluents are used. Generally speaking, suitable diluents / solvents for polymerization include non-coordinating inert liquids. Non-limiting examples generally include straight and branched hydrocarbons such as isobutane, butane, pentane, isopentane, hexane, isohexane, heptane, octane, dodecane and mixtures thereof; cyclic and alicyclic hydrocarbons such as cyclohexane, cycloheptane, methylcyclohexane, methylcycloheptane and mixtures thereof such as those present commercially (Isopar TM ); perhalogenated hydrocarbons such as perfluorinated C 4 To C 10Alkanes, chlorobenzenes and aromatic and alkyl-substituted aromatic compounds such as benzene, toluene, mesitylene and dimethylbenzene. Suitable solvents also include liquid olefins that can serve as monomers or comonomers, including but not limited to ethylene, propylene, 1-butene, 1-hexene, 1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-octene, 1-decene and mixtures thereof. In some preferred embodiments, aliphatic hydrocarbon solvents are used as solvents, such as isobutane, butane, pentane, isopentane, hexane, isohexane, heptane, octane, dodecane or mixtures thereof; Cyclic or alicyclic hydrocarbons, such as cyclohexane, cycloheptane, methylcyclohexane, methylcycloheptane or mixtures thereof.

[0097] Preferred polymerization processes can be run at any temperature and / or pressure suitable for obtaining the desired polyolefin. In a particular embodiment, the polyethylene composition is prepared in a slurry reactor (e.g., a slurry tank or slurry loop, preferably a slurry loop) maintained at a temperature in the range of 80 to 110° C., such as 82 to 108° C., 95 to 105° C., or 100 to 105° C.; or 95 to 110° C. The reactor pressure can be in the range of 425 to 800 psig (2930 to 5516 kPa), such as 450 to 650 psig (3102 to 4481 kPa); or 500 to 600 psig (3447 to 4137 kPa).

[0098] Hydrogen may be added to the reactor for molecular weight control of the polyolefin. In at least one embodiment, hydrogen is fed to the polymerization reactor such that it is present in the reactor at a molar concentration of about 0.1 to 2.1 mol%, such as 0.1 to 1.0 mol%.

[0099] In another class of embodiments, the polymerization process is a gas phase polymerization process. Generally, in a gas fluidized bed process for preparing a polymer, a gaseous stream comprising one or more monomers is continuously circulated through a fluidized bed in the presence of a catalyst under reactive conditions. The gaseous stream is discharged from the fluidized bed and recycled back to the reactor. At the same time, the polymer product is discharged from the reactor and fresh monomers are added to replace the polymerized monomers. Typically, a gas phase reactor can be operated in a condensing mode, wherein one or more of the above-mentioned diluents / solvents act as an inert condensing agent (ICA) in a fluidized bed reactor for heat removal to increase production rate and / or improve polymer properties. See, e.g., U.S. Patent Nos. 4,543,399; 4,588,790; 5,028,670; 5,317,036; 5,352,749; 5,405,922; 5,436,304; 5,453,471; 5,462,999; 5,616,661 and 5,668,228.

[0100] catalyst

[0101] As noted, suitable polymerization methods use polymerization catalysts. For example, the catalyst will preferably include chromium, chromium-containing or chromium-based catalysts. Chromium, chromium-containing or chromium-based catalysts are well-known and used for the polymerization of polyolefin polymers. Examples of two widely used catalysts include chromium oxide (CrO 3 ) and a silyl chromate catalyst, optionally containing at least one carrier. Chromium-containing catalysts have been the subject of much development in the field of continuous fluidized bed gas phase and slurry polymerization for preparing polyethylene polymers. Such catalysts and polymerization methods have been described, for example, in U.S. Patent Application Publication No. 2011 / 0010938 and U.S. Patent Nos. 2,825,721, 7,915,357, 8,129,484, 7,202,313, 6,833,417, 6,841,630, 6,989,344, 7,504,463, 7,563,851, 8,420,754 and 8,101,691.

[0102] Typically, the catalyst system comprises a supported chromium catalyst and a co-catalyst or activator. Generally speaking, a kind of such catalyst comprises a chromium compound supported on an inorganic oxide matrix. Typical carriers include oxides of silicon, aluminum, zirconium and thorium, and combinations thereof. Various grades of silicon dioxide and alumina carrier materials can be obtained from many commercial sources extensively.

[0103] In a particular embodiment, the support is silica. Suitable silicas generally have a good balance of high surface area and large particle size. These silicas are typically in the form of spherical particles obtainable by spray drying, or in the form of particles by grinding, and have a particle size of at least about 300 m 2 / g surface area and an average particle size of at least 25 microns. Methods for measuring surface area, pore volume and average particle size are disclosed in WO 2011 / 161412. For the preparation of higher molecular weight HDPE, typically about 500-600 m 2 / g together with modification with Al or Ti.

[0104] In several classes of embodiments, the silica support is rigid and has a large particle size averaging about 90-110 microns and extending up to at least 800 microns. 2 / g of high surface area. See, for example, WO 2011 / 161412. Without being bound by theory, the high surface area promotes the formation of a high molecular weight component, which provides improved physical polymer properties, especially stress cracking resistance, for high-load melt index products such as HDPE drums and intermediate bulk containers (IBCs). It also allows the use of low levels of Al or Ti modification for Cr / silica activated catalysts.

[0105] Commercially available silica supports include, but are not limited to, the support for PQ PD-11050 catalyst (880 m 2 / g surface area and 1.87mL / g pore volume); Support for PD-13070 catalyst (872m 2 / g surface area and 2.03 mL / g pore volume) and is available from PQ Corporation, Malvern, Pennsylvania. Previously, PQ silica was limited to about or less than 650 m 2 / g surface area such as their ES 70, CS2133 and CS2050, MS3065 silica. Alternatively, Sylopol 952, 955, 2408, etc. can be obtained from Grace Speciality Catalysts, WR Grace & Co., Columbia, Maryland.

[0106] In another embodiment, the support is a silica-titania support. Silica-titania supports are well known and described, for example, in U.S. Pat. No. 3,887,494. Silica-titania supports can also be prepared by "co-gelling" or co-precipitating silica and a titanium compound as described in U.S. Pat. Nos. 3,887,494, 5,096,868, and 6,174,981.

[0107] Suitable chromium-based catalysts, particularly titanium-modified chromium-based catalysts, are described, for example, in paragraphs

[0019] -

[0021] of U.S. Patent Publication No. 2020 / 0055966, the description of which is incorporated herein by reference.

[0108] In one class of embodiments, the chromium-based catalyst may be used optionally with at least one co-catalyst or activator. Generally, the co-catalyst may be a metal alkyl of a Group 13 metal. The co-catalyst may be of the formula MR 3 A compound wherein M is a Group 13 metal (according to the new numbering scheme of IUPAC), and each R is independently a linear or branched C 1 or C 2 or C 4 -C 12 or C 10 or C 8Alkyl. Mixtures of two or more such metal alkyls are also contemplated and are included in the term "promoter" as used herein. In various embodiments, M can be aluminum, and the promotor is at least one alkyl aluminum. Aluminum alkyls include triethylaluminum (TEAl), triisobutylaluminum (TIBAl), tri-n-hexylaluminum (TNHA), tri-n-octylaluminum (TNOA) and mixtures thereof. In another class of embodiments, at least one alkyl aluminum can be an alkoxylated alkyl aluminum compound, such as diethylaluminum ethoxide (DEAlE). In any of the above embodiments, the aluminum alkyl may be precontacted with at least one chromium-containing catalyst at an Al / Cr molar ratio of 0.01 to 10.00, at an Al / Cr molar ratio of 0.05 to 10.00, at an Al / Cr molar ratio of 0.05 to 8.00, at an Al / Cr molar ratio of 0.10 to 8.00, at an Al / Cr molar ratio of 0.10 to 5.00, at an Al / Cr molar ratio of 0.50 to 5.00, or at an Al / Cr molar ratio of 1.00 to 3.00.

[0109] Blends with PCR and other polymer materials

[0110] In some specific embodiments, the polyethylene composition prepared herein is combined in a blend with one or more other polymer compositions before forming a film, a molded part or other articles."blend" as used herein can refer to dry or extruder blends of two or more different polymers, and in-reactor blends, including blends produced in a single reactor zone using multiple or mixed catalyst systems, and blends produced under the same or different conditions in one or more reactors using one or more catalysts (e.g., blends produced in series reactors (same or different), wherein each reactor is operated under different conditions and / or with different catalysts).

[0111] In certain embodiments, the additional polymer composition(s) include post-consumer recycled (PCR) polymer material. Examples include, for example, homopolymer PCR (baby bottle resin) or mixed density HDPE PCR (e.g., a blend of recycled PE from various sources, possibly with up to 7 wt. % polypropylene in the blend). An example of a homopolymer PCR is KWR-101 resin, available from KW Plastics; examples of mixed density HDPE PCR include KWR-102 from KW Plastics.

[0112] In still other embodiments, blending partners with the polyethylene compositions of the present invention may include polyethylene, isotactic polypropylene, highly isotactic polypropylene, syndiotactic polypropylene, random copolymers of propylene and ethylene and / or butene and / or hexene, polybutene, ethylene-vinyl acetate, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), high density polyethylene (HDPE), ethylene-vinyl acetate, ethylene methyl acrylate, copolymers of acrylic acid, polymethyl methacrylate or any other polymer that can be polymerized by a high pressure free radical process, polyvinyl chloride, polybutene-1, isotactic polybutene, ABS resin, ethylene-propylene rubber (EPR), sulfurized EPR, ethylene propylene diene monomer (EPDM) polymers, block copolymers, styrenic block copolymers, polyamides, polycarbonates, PET resins, crosslinked polyethylene, copolymers of ethylene and vinyl alcohol (EVOH), polymers of aromatic monomers such as polystyrene, poly-1 esters, polyacetals, polyvinylidene fluoride, polyethylene glycol and / or polyisobutylene.

[0113] In some embodiments, the additional polymer (whether PCR polymer material or additional) is present in the above blend in an amount of 0.1 to 99 weight percent, based on the weight of the polymers in the blend, for example, in a range from a lower limit of any of 0.1, 0.5, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 weight percent to an upper limit of 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, or even 75 weight percent, with ranges from any of the foregoing lower limits to any of the foregoing upper limits being contemplated with the proviso that the upper limit is greater than the lower limit (e.g., 20 to 55 weight percent, 25 to 65 weight percent, 45 to 55 weight percent, 50 to 75 weight percent, 50 to 60 weight percent, etc.). The balance of the polymer blend of such embodiments may be the polyethylene composition of the various embodiments as previously described (wherein "balance" means wt % additional polymer + wt % polyethylene composition = 100 wt %). In a particular embodiment, the additional polymer is a PCR polymer material.

[0114] The above blends can be prepared by mixing the polyethylene composition with one or more additional polymers (as described above, and specifically including PCR materials), connecting reactors in series to prepare reactor blends or using more than one catalyst in the same reactor to prepare multiple polymer species. The polymers can be mixed together before being fed into the extruder or the polymers can be mixed in the extruder.

[0115] The blends can be formed using conventional equipment and methods, for example by dry blending the individual components and then melt mixing in a mixer, or by mixing the components directly together in a mixer such as a Banbury mixer, Haake mixer, Brabender internal mixer, or a single-screw or twin-screw extruder, which may include compounding extruders and side-arm extruders used directly downstream of a polymerization process, which may include blending powders or pellets of the resin at the hopper of a molding and / or film extruder.

[0116] Additionally, additives (e.g., described in more detail below) may be included in the blend, in one or more components of the blend, and / or in a product (e.g., a film) formed from the blend, as desired. These additives may include, for example: fillers; antioxidants (e.g., hindered phenolic compounds such as IRGANOX available from Ciba-Geigy); TM 1010 or IRGANOX TM 1076); phosphites (e.g., IRGAFOS available from BASF TM 168); acid scavengers; anti-adhesive additives; tackifiers, such as polybutene, terpene resins, aliphatic and aromatic hydrocarbon resins, alkali metal and glycerol stearates and hydrogenated rosin; UV stabilizers; heat stabilizers; anti-blocking agents; release agents; antistatic agents; pigments; colorants; dyes; waxes; silica; fillers; talc, etc.

[0117] In certain embodiments involving a 50 / 50 blend (i.e., 1:1 weight ratio) of a polyethylene composition and a PCR polymer material, the blend may exhibit any one or more of the following properties. In other words, the polyethylene composition according to various embodiments, when blended with a PCR material in a 1:1 weight ratio, exhibits one or more of the following properties:

[0118] Greater than 7, such as greater than 8 hours; for example, a Notched Constant Ligament-Stress (NCLS, 50°C, 600 psi) value in the range of 8 to 10, 12 or 15 hours. NCLS may be performed following ASTM F2136, wherein the sheet is prepared by compression molding according to ASTM D4703.

[0119] • MI is in the range of 0.1 to 1.0, for example 0.3 or 0.4 to 0.5, 0.6 or 0.7 g / 10 min.

[0120] • HLMI is in the range of 20, 30 or 40 to 50, 60 or 70 g / 10 min.

[0121] MIR is in the range of 70, 75, 80, 85, 90 or 95 to 100, 105, 110 or 115.

[0122] • Density in the range of 0.950, 0.951, 0.952, 0.953, 0.954, 0.955 or 0.957 to 0.960, 0.961, 0.962, 0.963, 0.964 or 0.965.

[0123] ESCR (100% Igepal) ranges from a lower limit of 25, 30, 32, 35, 36, 37, 38 or 39 hours to an upper limit of 45, 50, 55 or 60 hours.

[0124] • Flexural 1% Secant Modulus (ASTM D790, Procedure A) in the range of 135,000 to 160,000 psi; for example, 135,000 to 145,000 psi.

[0125] Izod impact strength (ASTM D256, Method A, at 23°C) is in the range of 0.90 or 0.94 to 1.2 Ft-lb / in.

[0126] - Izod impact strength (ASTM D256, Method A, at 18°C) within the range of 0.70 or 0.75 to 0.85 or 0.95 ft-lb / in.

[0127] Shore D hardness in the range of 55 or 60 to 65 or 70.

[0128] additive

[0129] The polyethylene compositions (and / or blends comprising the polyethylene compositions) of the present disclosure may include one or more additives. The additives may include reinforcing and non-reinforcing fillers, antioxidants, stabilizers, processing oils (or other solvent(s)), compatibilizers, lubricants (e.g., oleamide), antiblocking agents, antistatic agents, waxes, coupling agents for fillers and / or pigments, pigments, flame retardants or other processing aids, or combinations thereof (one or more).

[0130] The polyethylene composition of the present disclosure may include an additive such that the additive (e.g., a filler present in the composition) has an average agglomerate size of less than 50 microns, such as less than 40 microns, such as less than 30 microns, such as less than 20 microns, such as less than 10 microns, such as less than 5 microns, such as less than 1 micron, such as less than 0.5 microns, such as less than 0.1 microns, based on a 1 cm×1 cm cross-section of the cyclic polymer composition observed using a scanning electron microscope.

[0131] In at least one embodiment, the polyethylene composition may include fillers and colorants. Exemplary materials include inorganic fillers such as calcium carbonate, clay, silica, talc, titanium dioxide, or carbon black. Any suitable type of carbon black may be used, such as channel black, furnace black, thermal black, acetylene black, lamp black, etc.

[0132] In at least one embodiment, the polyethylene composition may include a flame retardant, such as calcium carbonate, an inorganic clay containing water of hydration, such as aluminum trihydroxide ("ATH"), or magnesium hydroxide.

[0133] In at least one embodiment, the polyethylene composition may include a UV stabilizer such as titanium dioxide or XT-850. The UV stabilizer can be introduced into the roofing composition as part of a masterbatch. For example, the UV stabilizer can be pre-blended into a masterbatch with a thermoplastic resin (e.g., polypropylene) or a polyethylene (e.g., linear low density polyethylene).

[0134] Still other additives may include antioxidants and / or heat stabilizers. In at least one embodiment, the processing and / or in-situ heat stabilizer may include the BASF B-225 and / or 1010.

[0135] In at least one embodiment, the polyethylene composition may include a polymer processing additive. The processing additive may be a polymer resin with a very high melt flow index. These polymer resins may include linear and / or branched polymers with a melt flow rate of about 500 dg / min or higher, such as about 750 dg / min or higher, such as about 1000 dg / min or higher, such as about 1200 dg / min or higher, such as about 1500 dg / min or higher. A mixture of various branched or various linear polymer processing additives, and a mixture of both linear and branched polymer processing additives may be used. Unless otherwise indicated, the polymer processing additives mentioned may include linear and branched additives. Linear polymer processing additives include polypropylene homopolymers, and branched polymer processing additives include diene-modified polypropylene polymers. Similar processing additives are disclosed in U.S. Patent No. 6,451,915, which is incorporated herein by reference.

[0136] In some embodiments, fillers (e.g., calcium carbonate, clay, silica, talc, titanium dioxide, carbon black, nucleating agents, mica, wood flour, etc., and blends thereof, as well as inorganic and organic nanoscale fillers) may be present in the polyethylene composition in an amount of about 0.1 wt % to about 10 wt %, such as about 1 wt % to about 7 wt %, such as about 2 wt % to about 5 wt %, based on the total weight of the polyethylene composition (or, where applicable, the total weight of the blend). The amount of filler that can be used may depend, at least in part, on the type of filler and the amount of extender oil used.

[0137] In some embodiments, and when employed, the polyethylene composition (and / or blend comprising the polyethylene composition) may include a processing additive (e.g., a polymer processing additive) in an amount from about 0.1 wt % to about 20 wt %, based on the total weight of the polyethylene composition (or, where applicable, the total weight of the blend).

[0138] Products

[0139] The polyethylene compositions of the present disclosure (and / or blends comprising the polyethylene compositions) can be used to form various articles, including film, sheet and fiber extrusion and coextrusion; and gas-assisted injection molding, extrusion blow molding, injection blow molding, injection stretch blow molding, compression molding, rotational molding, foam molding, thermoforming, sheet extrusion and profile extrusion. Molding methods are well known to those skilled in the art.

[0140] Suitable films may include monolayer or multilayer films, and they may also be blown or cast films formed by coextrusion or by lamination, and particularly include shrink films, cling films, stretch films, sealing films, oriented films, snack packaging, heavy-duty bags, grocery bags, baked and frozen food packaging, medical packaging, industrial liners, diaphragms, etc. in food contact and non-food contact applications. Fibers include melt spinning, solution spinning, and meltblown fiber operations for use in woven or nonwoven forms to make filters, diaper fabrics, medical garments, geotextiles, etc. Extruded products include medical tubing, wire and cable coatings, pipes, geomembranes, and pond liners. Molded products include single and multilayer buildings in the form of bottles, troughs, large hollow products, rigid food containers, and toys.

[0141] Tubular material (tubing) or pipe (pipe) can be obtained by profile extrusion, for medical treatment, drinking water, land drainage application or similar application. Tubular material or pipe can be unvulcanized or vulcanized. Vulcanization can be carried out using, for example, peroxide or silane during extrusion of the pipe. Profile extrusion method comprises extruding the molten polymer through a die head. Then the extruded tubular material or pipe is solidified into a continuous extruded product by cooling water or cooling air.

[0142] The enhanced properties of the polyethylene compositions (and / or blends comprising the polyethylene compositions) make them suitable for many end-use applications (e.g., films, molded articles, etc. formed from the compositions). Some examples include: transparent articles such as cooking and food storage utensils, and other articles such as furniture (e.g., outdoor and / or garden furniture), automotive components, toys, sportswear and sports equipment, medical devices, sterilizable medical devices and sterilized containers, nonwoven fibers and fabrics (and articles made therefrom such as curtains, gowns, filters, sanitary products, diapers, and films), oriented films, sheets, pipes, tubes, packaging, bags, bags, coatings, caps, closures, crates, pallets, cups, non-food containers, barrels, insulation, wire and cable jacketing, agricultural films, geomembranes, playground equipment, boat and watercraft components, and other such articles. In particular, the compositions are suitable for use in automotive components such as bumpers, grilles, trim components, fenders and fascias, exterior door and hood components, spoilers, wind deflectors, hubcaps, mirror housings, body panels, protective side moldings, and other interior and exterior components associated with automobiles, trucks, boats, and other vehicles.

[0143] Other examples of useful articles and goods may include: laboratory equipment, such as roller bottles and media bottles for growing cultures, office floor mats, instrument sample racks and sample windows; liquid storage containers, such as bags, packets and bottles for storing and IV infusion of blood or solutions; packaging materials, including packaging materials for medical devices or drugs, including unit dose or other blister or bubble packs, and packaging materials for packaging or containing foods preserved by irradiation. Other useful articles include packaging materials for irradiated medical devices or foods, including trays, and stored liquids, such as water, milk or juice containers, including unit service and bulk storage containers.

[0144] Extrusion coating

[0145] Polyethylene composition (and / or the blend comprising polyethylene composition) can be used in extrusion coating method and application.Extrusion coating is a plastic manufacturing method, wherein molten polymer is extruded and applied to a non-plastic carrier or substrate, for example on paper or aluminum to obtain a multi-material composite structure.This composite structure typically combines the toughness, sealing and impedance properties of a polymer formulation with the barrier, rigidity or aesthetic attributes of a non-polymer substrate.In this method, when extruding polymer from a slot die, typically substrate is fed into a molten polymer from a coil, which is similar to a cast film method.The resulting structure is cooled, typically cooled with a chill roll, and wound into a finished product roll.

[0146] Extrusion coated materials are typically used in food and non-food packaging, pharmaceutical packaging and in the manufacture of goods for the construction (insulating elements) and photographic industries (paper).

[0147] Foam products

[0148] The above-mentioned polymers and compositions (including polyethylene compositions and blends thereof) can be used in foaming applications. In the extrusion foaming method, a metering unit is utilized to inject a foaming agent, such as carbon dioxide, nitrogen, or a compound that decomposes to form carbon dioxide or nitrogen, into a polymer melt. Then in an extruder, the foaming agent is dissolved in the polymer, and the pressure is maintained during the entire period in the extruder. Rapid pressure drop rates produce foamed polymers with a homogeneous pore structure when leaving the extruder. The resulting foamed products are typically lightweight, tough, and are suitable for use in a wide range of applications in industry such as packaging, automobiles, aerospace, transportation, electrical and electronic instruments, and manufacturing. Example

[0149] Aggregation method description

[0150] Inventive Examples I-1, I-2 and I-3 are polyethylene compositions formed in a slurry loop reactor operated under the conditions as set forth in Table 1. After the polymerization process, the resulting slurry is separated from the diluent and dried. From there, the polymer is sent to a finishing section.

[0151] Table 1. Process conditions of the examples

[0152] Nature or condition Goal or scope pressure 550psig Hydrogen concentration (in reactor) 0.2-0.5mol% temperature 213-215°F Comonomer to ethylene feed ratio 8.5-10.0lb comonomer / 100lb ethylene Ethylene concentration 4.0-5.0wt%

[0153] Polymer properties

[0154] Tables 2a and 2b show the polymer properties (resin properties and physical properties, respectively) of Examples I-1, I-2 and I-3 of the present invention formed according to the above description. For comparison, Tables 2a and 2b also include the polymer properties (resin properties and physical properties) of Comparative Example C-1 (Paxon TM The same properties of C-2 (HD9830.2 HDPE, a bimodal HDPE available from ExxonMobil Chemical Company) and C-3 (HD9830.2 HDPE, a bimodal HDPE available from ExxonMobil Chemical Company). Each property in Tables 2a and 2b was measured as indicated in the table; where not indicated, the property was measured as previously detailed in connection with the description of the property in this disclosure. In addition, the molecular weight distribution of the inventive examples and comparative examples was determined via GPC4D (using conventional methods) according to the previous description of such measurement method. Figure 1 The resulting distribution is shown.

[0155] Table 2a. Resin properties - Inventive and comparative polymers

[0156]

[0157] Table 2b. Physical properties - polymers of the present invention and comparative examples

[0158]

[0159] The resin properties (Table 2a) show that the inventive examples of polyethylene compositions according to embodiments of the present disclosure have a substantial portion of high molecular weight polymer chains, while Figure 1 The resin is shown to retain its unimodal molecular weight distribution. In addition, Table 2a shows the favorable balance of properties achieved by the polyethylene compositions of the present invention, showing a blend of the best properties of bimodal and unimodal HDPE. Inventive Examples I-1, I-2, and I-3 all have close stress crack resistance values ​​comparable to bimodal C-2: the ESCR of the inventive samples at 10% Igepal ranges from 51.2 to 63.7 hours, which compares favorably to the 70.4 hours of bimodal C-2, while being significantly higher than the other unimodal HDPE, C-1; and the ESCR of the inventive samples at 100% Igepal ranges from 85 to 149.6 hours, which compares acceptably well to the 325.4 hours of bimodal C-2, and is several times higher than the 24.8 hours achieved by the other unimodal sample C-1 and 100% Igepal. Figure 3 and 4 The ESCR values ​​for 10% Igepal and 100% Igepal are shown respectively. On the other hand, the inventive sample outperforms the bimodal C-2 in the impact tests (Izod, Charpy Impact) while reaching similar values ​​as the unimodal C-1 in these properties.

[0160] Crystallinity

[0161] In addition, TREF was also performed as described previously herein for Inventive Examples I-1, I-2, and I-3 and Comparative Examples. Figure 2a and 2b and Table 3 further reports various values ​​associated with the TREF plot. The plots and values ​​reported in Table 3 confirm that the polyethylene composition of the present invention exhibits a multimodal crystalline fraction in TREF: as shown in Table 3 and Figure 2a and 2bAs can be seen in the Figure 1, the inventive example exhibits a main peak (T2) at about 96.73° and a very well defined "secondary" peak (T1) at about 89.05-89.37°C. This is in contrast to the bimodal HDPE C-2, which exhibits no secondary peaks on the TREF plot, and to the unimodal C-1, which exhibits a very small secondary peak, but at 91.45°C. Furthermore, the area under the curve A1 (defined as described previously in this specification) for example C-1 is only about 14.8%, compared to >20% for all the inventive examples tested, while the area A2 for C-1 is significantly larger compared to the inventive examples. As noted, because C-2 exhibits no secondary peaks, even the calculation of the relative areas associated with each peak cannot be performed.

[0162] Table 3. Crystallinity by TREF

[0163] nature C-1 C-2 I-1 I-2 I-3 <![CDATA[Peak area, A 1 (%)]]> 14.8 / 20.9 20.8 20.4 <![CDATA[Peak area, A 2 (%)]]> 84.8 99.3 78.0 78.2 78.6 Total integrated area (%) 99.6 99.3 98.9 99.0 98.9 <![CDATA[Peak maximum temperature, T 1 (°C)]]> 91.45 / 89.37 89.05 89.05 <![CDATA[Peak maximum temperature, T 2 (°C)]]> 96.89 98.17 96.73 96.73 96.73 <![CDATA[Peak minimum temperature, T 3 (°C)]]> 92.09 / 92.09 92.09 91.93 <![CDATA[ΔT 3 -T 1 (℃)]]> 0.6 / 2.7 3.0 2.9 <![CDATA[ΔT 2 -T 1 (℃)]]> 5.4 / 7.4 7.7 7.7

[0164] Stress crack resistance

[0165] The ESCR of the inventive resins was more extensively compared to other commercial unimodal HDPE examples at 100% Igepal ASTM D 1693 Condition B. The results are listed in Table 4 below (where MI and density are determined by ASTM D 1238 and ASTM D 1505, respectively). Figure 5 Density vs. MI is plotted for the inventive resins I-1 and I-2 and various comparative unimodal resins. Figure 5 In the above examples, C-1 is also Paxon AL55-003; C-3 is from Chevron Phillips Chemical. HHM 5502BN polyethylene; C-4 is Unival available from The Dow Chemical Company TM DMDA-6320NT7 HDPE resin; C-5 was purchased from Chevron Phillips Chemical 9512H polyethylene; C-6 is HP55-25-155 from Ineos; C-7 is Unival from The Dow Chemical Company TM DMDA-6200NT7. As can be seen, while the inventive resins conform to typical density / MI values ​​of other unimodal resins, they exhibit much superior ESCR (more than twice that of the closest unimodal commercial example), showing very surprising results for unimodal polyethylene compositions.

[0166] Table 4. ESCR relative to MI, density

[0167]

[0168] Rheology

[0169] The complex viscosities of C-1, C-2, and I-1 to I-3 at various shear rates were determined using SAOS measurements as described previously. Figure 6 is a plot of the complex viscosity of these samples. Figure 6 Shear thinning rheology is shown for all samples, but also shows advantageously lower complex viscosities at low shear rates for the inventive unimodal resins and bimodal C-2 compared to unimodal C-1, which shows another advantage obtained from unimodal resins 1-1, 1-2 and 1-3.

[0170] Blends

[0171] A 50 / 50 (wt%) blend of I-1 and PCR resin (KW Plastics Copolymer PCR KWR102MC resin, a mixed density recycled HDPE having the properties reported in Table 5 below) was prepared by dry blending the two resins in a cone blender and then melt blending in a twin screw extruder to ensure homogeneity. The resulting pellets were then compression molded into plaques and tested according to ASTM D4703. In addition, a 50 / 50 blend of C-1 and PCR, and a 50 / 50 blend of PCR and C-3 (as described above, this is a 50 / 50 blend from Chevron Phillips Chemical) were also prepared and tested. HHM5502BN); and PCR and C-8 (ExxonMobil TM The same is true for HDPE HYA 600 high density polyethylene). Table 5 below reports the properties of these blends.

[0172] Table 5. PCR blend properties

[0173]

[0174] In addition, C-1 alone, PCR alone, and PCR / I-1 blends were tested for stress crack resistance using the notched constant toughness stress (NCLS) test, following the method described previously for NCLS, using 10% Igepal at 50°C and using 600 psi pressure. PCR alone and C-1 alone were also tested. The results are reported in Table 6 below.

[0175] Table 6. Stress cracking resistance of PCR blends

[0176]

[0177] Normally, it is expected that PCR loading would degrade properties, but surprisingly, the 50 / 50 blend outperformed neat single peak C-1 in the NCLS assay. In addition, the PCR / I-1 blend provided significantly better ESCR and NCLS than other 50 / 50 blends prepared with C-1, C-8, and C-9.

[0178] Unless otherwise specified, the phrase "consisting essentially of" does not exclude the presence of other steps, elements, or materials (whether or not specifically mentioned in the specification), provided that these steps, elements or materials do not affect the basic and novel characteristics of the present disclosure, and further, they do not exclude impurities and variations normally associated with the elements and materials used.

[0179] For simplicity, only some numerical ranges are clearly disclosed herein. However, a certain lower limit can be used in combination with any other upper limit to limit the scope that is not clearly recorded. Similarly, a certain lower limit can be used in combination with any other lower limit to limit the scope that is not clearly recorded. Similarly, a certain upper limit can also be used in combination with any upper limit to limit the scope that is not clearly recorded. In addition, even if there is no clear description, each point or individual value between the two end points is also included in the scope. Therefore, each point or individual value itself can be used as a lower limit or upper limit in combination with other points or individual values ​​or other lower or upper limits to limit the scope that is not clearly recorded.

[0180] All documents described herein, including any priority documents and / or test procedures, are incorporated by reference in all jurisdictions not inconsistent with this document. It is apparent from the above overview and specific embodiments that, although the form of the present disclosure has been illustrated and described, various modifications can be made without departing from the spirit and scope of the present disclosure. Therefore, it is not desired that the present disclosure be limited in this manner. Similarly, the term "comprising" is considered synonymous with the term "including" with respect to U.S. law. Similarly, whenever a composition, element, or group of elements is preceded by the transitional term "comprising", it should be understood that the same composition or group of elements with the transitional term "essentially consisting of", "consisting of", "selected from" or "is" in front of the listed composition, element, or each element, and vice versa.

[0181] While the present disclosure has been described in terms of a number of embodiments and examples, those skilled in the art, after reading this disclosure, will appreciate that other embodiments can be devised without departing from the scope and spirit of the present disclosure.

Claims

1. A polyethylene composition comprising: 80 wt % to 99.9 wt % of ethylene units, and 0.1 wt % to 20 wt % of one or more C3 to C 40 Units of α-olefin comonomers, each weight % based on ethylene content plus C3 to C 40 α-olefin comonomer content; The polyethylene composition has: 0.935 to 0.975 g / cm 3 density; Melt index I determined according to ASTM D1238-13 Procedure B of 0.1 to 1 g / 10 min 2.16 ; Further wherein the polyethylene composition exhibits any one or both of: (i) environmental stress crack resistance in the range of 45 to 80 hours as measured according to ASTM D1693, 10% Igepal, Condition B and (ii) environmental stress crack resistance in the range of 70 to 250 hours as measured according to ASTM D1693, 100% Igepal, Condition B; and Further wherein the polyethylene composition has a unimodal molecular weight distribution, wherein the polyethylene composition has a high-to-low ratio in the range of 8 to 20, wherein the high-to-low ratio is defined as: Where HLMI is the high load melt index I determined according to ASTM D1238-13 Procedure B 21.6 , and η 低 It is the complex viscosity at 628 rad / s and 190°C.

2. The polyethylene composition of claim 1, wherein the C3 to C 40 The α-olefin comonomer includes 1-butene, 1-hexene, 1-octene or a combination thereof; Further wherein the ethylene content is from 98.5 wt% to 99.9 wt% and the comonomer content is from 0.1 wt% to 1.5 wt%, the wt% being based on the total mass of ethylene and comonomer content; and Further wherein the polyethylene composition has 2.0 to 5.0 ppm Cr and 6 to 15 ppm Ti, based on the total mass of the polyethylene composition.

3. The polyethylene composition of claim 1 or claim 2, further comprising: A weight average molecular weight Mw of 90,000 to 300,000 g / mol; A number average molecular weight Mn of 5,000 g / mol to 30,000 g / mol; 700,000 g / mol to 3.0x10 6 Z-average molecular weight Mz in g / mol; and Mz / Mn ratio of 125 to 300, Wherein Mw, Mn and Mz were determined by a method using high temperature gel permeation chromatography equipped with a multi-channel bandpass filter based infrared detector IR5, an 18-angle light scattering detector and a viscometer.

4. The polyethylene composition of claim 1 or claim 2, further comprising: Complex viscosity at 628 rad / s, 190°C from 200 to 800 Pa·s; Complex viscosity at 100 rad / s, 190°C of 3,000 Pa·s or less; A complex viscosity at 0.01 rad / s, 190°C of 80,000 Pa·s or less; and Shear thinning of 0.965 to 0.

990.

5. The polyethylene composition of claim 1 or claim 2, wherein the polyethylene composition further has: (a) an Izod impact strength of 1.8 to 2.5 Ft-lb / in at 23°C as determined in accordance with ASTM D256, Method A; (b) an Izod impact strength as measured at -40°C according to ASTM D256, Method A of 1.0 to 1.20 Ft-lb / in; and (c) 7 to 10.5 KJ / m 2 Charpy impact strength measured according to ISO 179_1 / 1eA.

6. The polyethylene composition of claim 1 or claim 2, further comprising: (a) Z plus 1 average molecular weight M of 2,750,000 g / mol to 4,500,000 g / mol z+1 ;and (b) Melt index ratio I of 80 to 94 21.6 / I 2.16 , where I 21.6 and I 2.16 Determined according to ASTM D1238-13 Procedure B.

7. The polyethylene composition of claim 1 or claim 2, wherein the polyethylene composition exhibits a notched constant band stress in the range of 13 to 20 hours according to ASTM F2136 at 10% Igepal, 50°C, 600 psi.

8. The polyethylene composition of claim 1 or claim 2, wherein the polyethylene composition exhibits multiple distinct crystalline fractions as determined by Temperature Rising Elution Fractionation (TREF).

9. The polyethylene composition of claim 8, wherein the plurality of distinct crystalline fractions comprises a first crystalline fraction having a peak at T1 on the TREF curve and a second crystalline fraction having a peak at T2 on the TREF curve; wherein: The local minimum on the TREF curve at T3 is defined by the valley between the peaks of the first and second crystalline fractions; and T1 ranges from 85°C to 94°C, T2 ranges from 96°C to 99°C; and T3 ranges from 87°C to 96°C, provided that T3-T1>1°C and T2-T1>5.5°C.

10. The polyethylene composition of claim 9, wherein T3 - T1 > 2°C and T2 - T1 > 7°C.

11. The polyethylene composition of claim 10, wherein the area A1 under the TREF curve bounded by T=40°C and T=T3 and the area A2 under the TREF curve bounded by T=T3 and T=120°C are such that A1 is at least 15% of the total area A1+A2.

12. A polyethylene composition having 95 to 99.9 wt% of ethylene units and 0.1 to 5 wt% of C3 to C 20 The polyethylene composition comprises: 0.935 to 0.975 g / cm 3 density; A unimodal molecular weight distribution as determined by GPC4D; and Multiple distinct crystalline fractions determined by temperature rising elution fractionation TREF; in: (a) the plurality of different crystalline fractions comprises a first crystalline fraction having a peak at T1 on the TREF curve and a second crystalline fraction having a peak at T2 on the TREF curve; wherein: A local minimum on the TREF curve at T3 defines a valley between the peaks of the first and second crystalline fractions; and T1 is in the range of 88°C to 92°C, T2 is in the range of 94°C to 100°C, and T3 is in the range of 91°C to 94°C; with the further proviso that T3-T1 >1°C and T2-T1 >5.5°C; and (b) The area A1 bounded by T=40°C and T=T3 under the TREF curve and the area A2 bounded by T=T3 and T=120°C under the TREF curve are such that A1 is at least 15% of the total area A1+A2.

13. The polyethylene composition of claim 12, having one or more of the following properties: (a)1.0x10 6 g / mol to 3.0x10 6 Z-average molecular weight Mz in g / mol; (b) a Mz / Mn ratio of 125 to 300; (c) Melt index I measured according to ASTM D1238-13 Procedure B of 0.1 to 10 g / 10 min. 2.16 ;and (d) Environmental stress crack resistance in the range of 70 to 200 hours as determined according to ASTM D1693 at 100% Igepal, Condition B.

14. The polyethylene composition of claim 13 having all of properties (a) to (d).

15. The polyethylene composition of claim 12 or claim 13, further having a high-low ratio in the range of 8 to 20, wherein the high-low ratio is defined as: Where HLMI is the high load melt index I determined according to ASTM D1238-13 Procedure B 21.6 , and η 低 It is the complex viscosity at 628 rad / s and 190°C.

16. A blend comprising the polyethylene composition of any preceding claim and post-consumer recycled PCR polymer material.

17. The blend of claim 16, comprising 25 to 65 weight percent of post-consumer recycled PCR polymer material and 35 to 75 weight percent of the polyethylene composition, the weight percents being based on the total amount of PCR polymer material and polyethylene composition in the blend.

18. The blend of claim 17 having an environmental stress crack resistance at 100% Igepal in the range of 25 to 60 hours.

Citation Information

Patent Citations

  • Modified Chromium-Based Catalysts and Polymerization Processes for Using the Same

    US20110010938A1

  • Polymerization Processes Utilizing Chromium-Containing Catalysts

    US20200055966A1

  • Bimodal PE Resins with Improved Melt Strength

    US20200115533A1

  • High-density ethylene-based polymer using hybrid supported metallocene catalyst and pipe using same

    US20200190238A1

  • Methods for Improving Color Stability in Polyethylene Resins

    US20200224014A1